Strengthening Policy Capacity and Human-Centric Approaches Drives Successful Smart Governance Implementation - Muhammad Zikri; Eko Prasojo (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Smart governance is a key pillar in smart city development, requiring not only technological advancement but also sufficient policy capacity and supportive organizational factors such as innovation culture, human-centric approaches, and collaboration. This study analyzes policy capacity and success factors of smart governance implementation in Tangerang City. Using a qualitative case study approach, this research applies the policy capacity framework and the smart governance success factor. The findings indicate that while the Tangerang City Government demonstrates relatively strong operational capacity and innovation performance, analytical capacity remains constrained by data quality and limited analytical human resources. Moreover, human-centric design, digital culture sustainability, and collaborative governance have not yet been fully institutionalized. This study concludes that strengthening policy capacity in conjunction with innovation culture, digital literacy, and collaborative governance is essential to achieving transformative and sustainable smart governance. The findings imply that local governments should invest strategically in human resource development, improve data governance and analytical capabilities, and prioritize user-centric digital services to enhance the effectiveness, responsiveness, and inclusiveness of smart governance initiatives.